2012
DOI: 10.1177/0022146512439453
|View full text |Cite
|
Sign up to set email alerts
|

Associative Stigma among Mental Health Professionals

Abstract: In contrast with growing attention given to the stigma experiences of mental health service users, the stigma literature has paid almost no attention to mental health professionals. This study focuses on experiences of associative stigma among these professionals. We investigate the link between associative stigma and three dimensions of burnout as well as job satisfaction among mental health professionals, and the link of associative stigma with self-stigma and client satisfaction among service users. Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 73 publications
(100 reference statements)
0
56
0
1
Order By: Relevance
“…Because cultural stigma beliefs are a societal feature, our research provides further evidence that stigma might pose an important threat, both to individual health and to public health in general (Link and Phelan, 2006). The effects of stigma beliefs that are embedded within a common culture are not limited to the effectiveness of specific mental health services (Rosenfield, 1997;Sirey et al, 2001;Verhaeghe et al, 2010;Verhaeghe and Bracke, 2012). They are also likely to affect the mental health of the population as a whole, as stigma acts as a barrier to professional mental health support for individuals who are currently in need of such support, as well as for those who might need it in the future.…”
Section: Discussionmentioning
confidence: 77%
“…Because cultural stigma beliefs are a societal feature, our research provides further evidence that stigma might pose an important threat, both to individual health and to public health in general (Link and Phelan, 2006). The effects of stigma beliefs that are embedded within a common culture are not limited to the effectiveness of specific mental health services (Rosenfield, 1997;Sirey et al, 2001;Verhaeghe et al, 2010;Verhaeghe and Bracke, 2012). They are also likely to affect the mental health of the population as a whole, as stigma acts as a barrier to professional mental health support for individuals who are currently in need of such support, as well as for those who might need it in the future.…”
Section: Discussionmentioning
confidence: 77%
“…These findings are consistent with past research, which has found that stigmatization towards patients among mental health workers is associated with more self-stigma and poorer job satisfaction. [22] Additionally, stigma towards BPD patients at baseline predicted client burnout following training, even after controlling for pretreatment burnout levels. In contrast, pre-treatment burnout did not significantly predict BPD stigma following training.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these participants were sensitive to negative experiences, including SBA, and thus avoided social experiences and social events to reduce the risk of rejection and stress (Philips & Benoit, 2013). Withdrawal from one's social network and social events might also have been necessary to prevent emotional exhaustion (Verhaeghe & Bracke, 2012).…”
Section: Stigma By Associationmentioning
confidence: 99%